Financial Literacy, Financial Parenting, and Riba Awareness: Drivers of BNPL Use Among Muslim Youth - Marheni, Dewi Khornida; Widiyanti, Riski; Haryanto, Hery; Cruz II, Roque B. (Universitas Ahmad Dahlan, 2025)
This study explores the effect of financial literacy, financial parenting, and knowledge about riba on Muslim consumer behavior using Buy Now Pay Later (BNPL) services, with financial self-efficacy and perceived risk of usury as mediators. Through a mixed approach (quantitative on 402 Muslim respondents of generation Y and Z with formal Islamic education and qualitative through interviews with six informants), this study found that financial literacy does not directly affect the use of BNPL. However, financial parenting significantly increases financial self-efficacy, which drives using BNPL. In addition, understanding riba increases the perception of usury risk, ultimately reducing the intention to use BNPL. The implications of this study highlight the importance of financial education in the family and understanding of Islamic values in shaping responsible consumer behavior, as well as its relevance for Islamic financial policy and education.